2006
DOI: 10.2105/ajph.2004.057075
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment in Early Life and Mental Health Problems in Adulthood

Abstract: Subaverage cognitive functioning in early life increases later risk of mental health problems. Future research may help to delineate possible impediments faced at different developmental stages and guide changes in supportive services to better address the needs of children with borderline mental retardation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…The prevalence of mental health problems among people with BIF was reported in four studies (Chen, Lawlor, Duggan, Hardy, & Eaton, 2006;Emerson, Einfeld, & Stancliffe, 2010;Hassiotis et al, 2008). Whether comparing already existing diagnoses (Chen et al, 2006) or symptoms of the mental health problems Emerson et al, 2010;Hassiotis et al, 2008), mental health problems were more prevalent among subjects with BIF than among the general population (Table 4). Although Dekker and Koot did not include a control group in their study, they concluded that the prevalence of most mental disorders among subjects with BIF exceeded the prevalence that was observed in the general population.…”
Section: Mental Healthmentioning
confidence: 95%
See 2 more Smart Citations
“…The prevalence of mental health problems among people with BIF was reported in four studies (Chen, Lawlor, Duggan, Hardy, & Eaton, 2006;Emerson, Einfeld, & Stancliffe, 2010;Hassiotis et al, 2008). Whether comparing already existing diagnoses (Chen et al, 2006) or symptoms of the mental health problems Emerson et al, 2010;Hassiotis et al, 2008), mental health problems were more prevalent among subjects with BIF than among the general population (Table 4). Although Dekker and Koot did not include a control group in their study, they concluded that the prevalence of most mental disorders among subjects with BIF exceeded the prevalence that was observed in the general population.…”
Section: Mental Healthmentioning
confidence: 95%
“…Based on three studies, the risk of BIF somewhat increased with low birth weight (LBW). The prevalence of LBW in the adult BIF population was higher (24%) than in the average intelligence population (13%) in the study of hospital birth cohorts (Chen et al, 2006). The prevalence of BIF in the group of 3-year-old children with LBW was 19% (Ramey et al, 1992).…”
Section: Risk and Preventive Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies of bipolar disorder have largely shown no association with premorbid IQ (5, 7, 8), but one study of U.S. Army recruits found elevated IQ scores in bipolar patients (9). Low IQ has been associated with increased risk of substance use disorders in some study groups (6, 10) but not in others (11-13). In one cohort, the association between low childhood IQ and increased risk of any anxiety disorder was attenuated to nonsignificance once other covariates were included (11).…”
mentioning
confidence: 87%
“…Both children and adults with confirmed borderline intellectual functioning have been shown to be more represented in populations with greater psychopathological risk (Masi, 1998;Ninivaggi, 2001), in populations demonstrating vocational and school problems (Dunham & Schrader, 2000), and in populations with an increased likelihood of multidrug pharmacotherapy for disruptive behavior disorders (Stolker et al, 2001). Borderline intellectual functioning has also been demonstrated as a common comorbidity (Ferrari, 2007;Handen, Janosky, & McAuliffe, 1997) and a challenging factor for quality of life in medical treatments (Chen et al, 2006). Despite notable exceptions (e.g., Tymchuck, Lakin, & Luckasson, 2001), few books have systematically addressed the social, psychological, and contextual circumstances of persons with these types of ''mild'' cognitive impairments.…”
Section: Research On Borderline Intellectual Functioningmentioning
confidence: 99%